Beach-face morphodynamics of different morphological setting along Teluk Chempedak to Kuala Pahang, Malaysia - Mustapa, Mohd Zaini; Saad, Shahbudin; Abdul Hadi, Muhammad Salihi; Yunus, Kamaruzzaman (Universiti Teknologi Malaysia, 2015)
The present study on beach morphology and its profile dynamics was carried out to categorize the morphodynamic classification of selected beaches in Pahang, comprising the areas from Teluk Chempedak to Kuala Pahang. Beach stations were monitored monthly for a complete 1-year cycle; beginning from February 2012 to February 2013 at 12 corresponding stations established at random morphological intervals. Based on the results obtained, which include the granulometric analysis and beach surface topography, three main beach classes have been differentiated: reflective, intermediate and dissipative beaches. The reflective beaches exhibits rather high degree beach slopes and coarse-grain sand sizes compared to intermediate and dissipative classes.